KONTRIBUSI KEPUASAN DAN SEMANGAT KERJA TERHADAP KINERJA GURU SDN AMUNTAI HULU SUNGAI UTARA - Siti Rahmah (Jurnal Pendidikan Kewarganegaraan, 2016)
The quality of education is closely linked to the performance of teachers as educators in educational institutions with due regard to job satisfaction and morale. Aims this study to shopped determine the contribution to the performance of job satisfaction, morale on the performance, as well as job satisfaction and morale together on teacher performance Amuntai Elementary School (SD) in the city. This study is an ex-post facto study using a quantitative approach. The population in this study are all elementary school teachers with the 186 SD scattered in 10 subdistricts. Data obtained using a questionnaire that was analyzed descriptively continued with the analysis of multiple regression. Descriptive analysis revealed that was job satisfaction of teachers (X1) SDN Amuntai city is relatively high, the morale of teachers (X2) was relatively high enough, and performance teachers (Y) is relatively enough. The results of the analysis of multiple regression showed the magnitude of R2 X1 to Y at 0.286, R2 X2 to Y at 0.102. Besides, the analysis also showed a positive and significant contribution to the results of the F-hit 79.600 respectively, 22, 80 and 42, 379 in sig 0,000. Keywords: job satisfaction, morale, performance, teacher.